Studies in Mexican Tettigoniidae: A new genus of Copiphorini and the first description of male Conocephalus (Aphauropus) leptopterus Rehn and Hebard and the female of Insara acutitegmina Fontana, Buzzetti, Mariño-Pérez & García García - Fontana, Paolo; Mariño-Pérez, Ricardo; Woller, Derek A. (Zootaxa, 2013)
A new genus belonging to the katydid tribe Copiphorini (Tettigoniidae: Conocephalinae) is established, Brachycaulopsis gen. nov., collected from the state of Chiapas, Mexico. Also provided are first descriptions for both the male of Conocephalus (Aphauropus) leptopterus Rehn & Hebard, 1915 (Conocephalinae: Conocephalini) and the female of Insara acutitegmina Fontana et al., 2011 (Phaneropterinae: Insarini).